Environmental chemistry of the heavy elements : hydrido and organo compounds - Thayer, John S (New York, N.Y. : VCH, 1995)
Environmental Chemistry of the Heavy Elements provides a critical review and discussion of roles played by hydrides and alkyls of the heavier elements in the natural environment. Research into the environmental chemistry of alkylmetal and alkyllmetalloid compounds has been steadily expanding and diversifying over the past three decades. Unexpected vistas have opened up with the recent discovery that hydride derivatives of many of these same elements also form and exist under environmental conditions. This book also discusses roles that microorganisms play in the formation, distribution, and degradation of heavy element compounds, and points out future possibilities and needs in this field. Environmental Chemistry of the Heavy Elements will be of interest to environmental scientists, geochemists, toxicologists, certain biotechnology professionals, and persons interested in waste recycling
1. Introduction -- 2. Selected Physical and Chemical Properties -- 3. Hydrides: Sources in the Environment -- 4. Alkyls: Sources in the Environment -- 5. Mechanisms: I. Biohydridization and Biomethylation -- 6. Mechanisms: II. Bioalkylation, Biotransformation, and Biodealkylation -- 7. Hydrides and Alkyls: Their Roles in Geochemical Cycles -- 8. Hydrides and Alkyls: Their Roles in Biogeochemical Cycles -- 9. Potential Applications and Possible Future Developments
Includes bibliographical references and indexes
Keywords: Heavy elements -- Environmental aspects; Hydrides -- Environmental aspects; Organometallic compounds -- Environmental aspects